2019
DOI: 10.5334/aogh.2565
|View full text |Cite
|
Sign up to set email alerts
|

First Year Medical Students, Personal Handheld Ultrasound Devices, and Introduction of Insonation in Medical Education

Abstract: Background:Ultrasound education has been provided to students in medical schools within and beyond the United States. A formal experiment with use of personal handheld ultrasound equipment by all first-year medical students has not been reported. Employing insonation (an application of ultrasound) at the personal leisure by medical school freshmen enables self-directed learning throughout the academic year.Methods:We describe a peer-led ultrasound curriculum with handheld devices. The students’ perceptions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
4
24
0
3
Order By: Relevance
“…With regard to the results of survey response when the participants were asked to evaluate their ultrasound learning experience while using the HHU device, the study showed agreement with respect to most items. These results were consistent with findings from a study by Ireson et al [6], who had provided all of their 1 st year medical students with HHU devices. On their baseline survey, overall agreement was observed for the following criteria: (1) Enhancement on performance of ultrasounds (62.5%), (2) interpretation of ultrasounds (56.3%), (3) understanding anatomy (68.8%), (4) learning anatomy (61.3%), (5) ease (78.1%), (6) comfort (59.4%), and (7) the benefits provided by the incorporation of insonation into the medical school curricula.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the results of survey response when the participants were asked to evaluate their ultrasound learning experience while using the HHU device, the study showed agreement with respect to most items. These results were consistent with findings from a study by Ireson et al [6], who had provided all of their 1 st year medical students with HHU devices. On their baseline survey, overall agreement was observed for the following criteria: (1) Enhancement on performance of ultrasounds (62.5%), (2) interpretation of ultrasounds (56.3%), (3) understanding anatomy (68.8%), (4) learning anatomy (61.3%), (5) ease (78.1%), (6) comfort (59.4%), and (7) the benefits provided by the incorporation of insonation into the medical school curricula.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in a pilot programme at the Mayo Clinic Alix School of Medicine, 53 first-year medical students were provided with a handheld POCUS device for their personal use for 1 year. 21 The POCUS devices were received enthusiastically by students and were considered easy to use and a valuable tool to improve their understanding of three-dimensional anatomy. 21 In the present study, final-year medical students involved in day-to-day patient care on assigned medical wards were provided with a personal handheld POCUS device (1 device per 3 students) during the 8-week period of Internal Medicine rotation.…”
Section: Discussionmentioning
confidence: 99%
“…21 The POCUS devices were received enthusiastically by students and were considered easy to use and a valuable tool to improve their understanding of three-dimensional anatomy. 21 In the present study, final-year medical students involved in day-to-day patient care on assigned medical wards were provided with a personal handheld POCUS device (1 device per 3 students) during the 8-week period of Internal Medicine rotation. Similar to the prior report in first-year medical students undertaking an anatomy course, the personal handheld POCUS device was enthusiastically received by medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac POCUS in Medical Education Over the past decade, there has been great interest in integrating ultrasound education to augment training in medical schools and residency programs across the USA. In the undergraduate medical education setting, ultrasound education can be favorably incorporated into the traditional preclinical curriculum to consolidate learning of anatomy, physiology, pathophysiology, and physical examination [46][47][48]. In fact, first-year medical students who used handheld ultrasound as part of their curriculum reported greater spatial understanding of anatomy and perceived ultrasound to be a valuable tool to use in their future careers [47].…”
Section: Role Of Pocus In Various Settingsmentioning
confidence: 99%
“…In the undergraduate medical education setting, ultrasound education can be favorably incorporated into the traditional preclinical curriculum to consolidate learning of anatomy, physiology, pathophysiology, and physical examination [ 46 48 ]. In fact, first-year medical students who used handheld ultrasound as part of their curriculum reported greater spatial understanding of anatomy and perceived ultrasound to be a valuable tool to use in their future careers [ 47 ]. POCUS can also be employed to improve diagnostic skills for upper-level medical students during their clinical rotations.…”
Section: Role Of Pocus In Various Settingsmentioning
confidence: 99%